"Forgiving" God: Reflections on Psychological Research Describing Spiritual Struggle. Issue 3 (October 2014) - Webb, Marcia
In A Grief Observed, when contemplating his wife's death, C.S. Lewis described his fear of "coming to believe … dreadful things about [God]." 1 Psychological research has noted that, when suffering, people may experience anger or disillusionment with God. These experiences are also demonstrated in biblical characters like Moses, Jeremiah, and Job. This article describes the use of the term "forgiveness" in the psychological process of the resolution of anger with God for release from this type of spiritual struggle. Yet "forgiving" God may seem illogical, given conceptions of divine perfection. The author further describes the developmental processes in resolution of anger toward God which are both affective and cognitive, involving the accommodation of new "God concepts" with the challenging new experiences of suffering and injustice.